Perlindungan Terhadap Petugas Medis di Daerah Konflik Berdasarkan Hukum Humaniter Internasional (Studi Kasus Perawat Palestina Razan Al Najjar yang di Tembak Mati Oleh Tentara Israel Pada Tahun 2018) - Pratama, Lorenci Chakti; Novianti, Novianti; Pebrianto, Dony Yusra (Faculty of Law, Universitas Jambi, 2021)
War or armed conflict is a legitimate step to resolve various problems when peaceful methods can no longer find a solution. Armed disputes are regulated in the 1949 Geneva Conventions and the 1977 Additional Protocols. An armed dispute is sure to bring tremendous suffering to mankind. Millions of people, both military and civilian, were victims. The result of armed conflict is that there are many victims, so medical officers are urgently needed to provide assistance and care for war victims. But in reality there are still many violations against medical personnel. Medical personnel are deliberately targeted for attack by the parties to the dispute, even though the Geneva Conventions I 1949 and the 1977 Additional Protocol clearly state that medical personnel must always be respected and protected and should not be the object of attack. This study attempts to analyze the forms of legal protection for medical personnel in the Geneva Conventions of 1949 and Additional Protocol II 1977 and the factors that cause the disputing parties to not comply with the rules of International Humanitarian Law on the protection of medical personnel. So that the results of this study can provide some clarity about the forms of legal protection for medical personnel and the factors that cause violations of humanitarian law against the protection of medical workers.